Sympathy for the devil [videorecording (DVD)] - Paradise, Luke; Cage, Nicolas, 1965-; Kinnaman, Joel, 1979- (RLJ Entertainment, 2023)
After being forced to drive a mysterious passenger at gunpoint, a man finds himself in a high-stakes game of cat and mouse where it becomes clear that not everything is as it seems.